A randomized split-face clinical trial of conventional vs indoor-daylight photodynamic therapy for the treatment of multiple actinic keratosis of the face and scalp and photoaging. (19th May 2022) - Arisi, M.; Rossi, M. T.; Spiazzi, L.; Guasco Pisani, E.; Venturuzzo, A.; Rovati, C.; Tomasi, C.; Venturini, M.; Calzavara-Pinton, P. G.
Abstract: Background: Recently, indoor daylight photodynamic therapy (idl-PDT) has been developed; however, its efficacy and tolerability remain to be assessed. Objective: This is a not-inferiority study to compare treatment outcomes of cPDT with a red LED lamp and idlPDT with a polychromatic white LED lamp in adult patients affected by symmetrical AKs of face and/or scalp. Methods: In this comparative, intra-patient, split-face, randomized clinical trial forty-three adult patients were enrolled. Two contralateral and symmetrical target areas of the face and/or scalp harboring at least 5 AKs were selected and randomized 1:1 to treatment with cPDT and idlPDT. The AKs number and cumulative area were assessed at baseline (T0). Efficacy and cosmetic outcome were assessed 3 months after treatment (T1). Results: Total AKs number and area reduced significantly with both idlPDT ( p  < .0001) and cPDT ( p  < .0001) in comparison to baseline. cPDT was more painful ( p  < .0001) and induced a more severe inflammation ( p  < .0001). Twenty-nine patients (70.7%) gave their overall preference to idlPDT ( p  < .001). Conclusion: idlPDT may represent an alternative treatment protocol to cPDT for in-office treatment of AKs patients with better tolerability and a not inferior efficacy.